Trends in cannabis use disorder and treatment by race and ethnicity, 2002–2019 - Triguero Roura, Mireia; Vora, Aabha; Eschliman, Evan L.; Mauro, Pia M. (Frontiers in Psychiatry, 2025)
Aims/backgroundAs cannabis use continues to increase in the United States, racialized stereotypes and structural barriers to care might lead to inequitable treatment uptake across racialized groups. A greater understanding of racial disparities in cannabis treatment uptake and perceived treatment need among people with cannabis use disorder (CUD) in community-based samples is needed.MethodsNationally representative data from the 2002–2019 National Survey on Drug Use and Health (N=1,005,421) included community-based people ages 12+ First, we assessed trends in CUD (i.e., meeting 2+ DSM-5 proxy CUD criteria) by racialized group. Among people with CUD (n=48,768), weighted logistic models regressed any CUD treatment, specialty CUD treatment, and perceived need for CUD treatment on racialized group and year, adjusting for age, gender, education, insurance, and criminal legal system exposure. We use interaction terms to examine group-specific trend differences.ResultsOverall, 2.64% of the US population ages 12+ had CUD, including 2.47% of white, 1.23% of AAPI (Asian American and Pacific Islander), 4.83% of AIAN (American Indian and Alaska Native), 3.70% of Black, and 2.71% of Hispanic people. CUD increased slightly across all groups (overall annual OR: 1.01, 95% CI =1.01,1.02), with AAPI, Hispanic and people with more than one race seeing steeper increases (ORs: 1.02-1.04). Treatment use and perceived need decreased consistently and there were no group differences in these trends across racialized groups with CUD (ORs: 0.93-0.97). Black people with CUD had 21% lower odds of any treatment than white people (aOR: 0.79, 95% CI=0.65, 0.95). All racialized groups (except AAPI people) had higher odds of perceived need than white people (aORs: 1.59–1.73).ConclusionAlthough all racialized groups had increasing CUD and decreasing CUD treatment use during the study period, the observed racialized disparities also persisted. For example, despite a higher prevalence of CUD among Black people compared to white people, Black people with CUD were less likely than their white counterparts to receive treatment and more likely to report perceived need. These disparities in CUD, treatment use, and perceived need underscore the need for CUD-related services overall and tailored services for racialized minorities, and especially Black people.